Financial education in schools: A meta-analysis of experimental studies - Tim Kaiser; Lukas Menkhoff (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
We study the literature on school financial education programs for children and youth via a quantitative meta-analysis of 37 (quasi-) experiments. We find that financial education treatments have, on average, sizeable impacts on financial knowledge (+0.33 SD), similar to educational interventions in other domains. Additionally, we document smaller effects on financial behaviors among students (+0.07 SD). When restricting the sample to 18 randomized experiments average effect sizes are estimated to be about 0.15 SD units on financial knowledge and 0.07 SD units on financial behaviors. These results are robust irrespective of the meta-analytic method used and when accounting for publication bias. Subgroup analyses show the beneficial effect of more intensive treatments, albeit with decreasing marginal returns.
Keywords: I21; A21; D14; 330; financial education; financial literacy; financial behavior; meta-analysis